Perlindungan Peserta Magang terhadap Uang Saku: Analisis Implementasi Peraturan Ketenagakerjaan dan Teori Keadilan John Rawls - Nuzulul, Khansa; Author, Ahmad Nailul (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2025)
This research focuses on the issue of providing allowances to internship students, analyzed through the framework of labor law regulations and John Rawls theory of justice. Undergraduate student internships are crucial for national growth because they can foster creativity and human resource potential. To improve competence and competitiveness, internship programs serve as a strategic link between institutions, students, and education. However, internship practices in Indonesia were often abused through unpaid internships or by providing very low allowances, which led to unfair treatment of interns. The Indonesian legal framework regulates internships through Law Number 13 of 2003 and examines Law Number 20 of 2003 concerning the National Education System (Sisdiknas), which serves as the main reference in Permendikbudristek Number 63 of 2024 concerning the Implementation of Student Internships. This study uses a normative juridical approach with a qualitative analysis of relevant regulations, in which Rawl’s theory of justice serves as a normative evaluative tool in assessing the implementation of the regulations. The results show that although the legal framework is relatively clear, its implementation does not fully reflect Rawls's principles of equal opportunity and the difference principle. Unpaid internships exacerbate inequality and place a disproportionate burden on economically vulnerable groups. Penelitian ini memfokuskan pembahasan pada pemberian uang saku kepada mahasiswa berdasarkan aturan ketenagakerjaan dan teori keadilan John Rawls. Mahasiswa magang sangat penting bagi pertumbuhan negara untuk meningkatkan kompetensi dan daya saing, program magang memiliki fungsi sebagai penghubung strategis antara institusi, mahasiswa, dan pendidikan. Namun, praktik magang di Indonesia sering disalahgunakan dengan tidak dibayarnya atau dengan memberikan uang saku yang sangat rendah yang menyebabkan perlakuan tidak adil terhadap peserta magang. Kerangka hukum Indonesia telah mengatur magang melalui UU Nomor 13 Tahun 2003 serta mengkaji Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional (Sisdiknas) yang menjadi rujukan utama dalam Permendikbudristek Nomor 63 Tahun 2024 tentang Penyelenggaraan Magang Mahasiswa. Penelitian ini menggunakan pendekatan yuridis normatif dengan analisis kualitatif di mana teori Rawls berfungsi sebagai alat evaluasi normatif dalam implementasi regulasi. Hasil penelitian menunjukkan bahwa meskipun kerangka hukum relatif jelas, implementasinya belum sepenuhnya mencerminkan prinsip-prinsip Rawls tentang kesempatan yang sama dan prinsip perbedaan. Magang yang tidak dibayar memperburuk ketimpangan dan memberikan beban yang tidak proporsional pada kelompok rentan secara ekonomi